The role of digital therapeutics in healthcare systems - van Dam, Joris (Henry Stewart Talks, 2024)
Digital therapeutics, The role of digital therapeutics in healthcare systems, Improved patient experience, Better outcomes, Lower cost of care, Improve provider well-being, Improve health equity